Pondering with Örö Pines : Talking with Trees as an Undisciplinary Method - Arlander, Annette (The White Horse Press, 2025)
This text presents talking with trees as a method of generating material for artistic and other research purposes based on conversations with pine trees recorded in May 2022 on Örö Island in southwestern Finland. Addressing one pine tree a day for six consecutive days as part of the project Pondering with Pines was an experiment that resulted in video works and podcast episodes. The perspective was human centred and subjective while also subjectifying the trees. In this context, the focus is on talking with trees as an undisciplinary method adaptable to other circumstances.
Keywords: puut (kasvit); taiteellinen tutkimus; esittävät taiteet; performanssi; taide; taiteellinen työ